Towards synergy between spin-crossover and metal–ligand bond break in molecular crystals: structural investigations of eight seven-coordinated Fe(ii) macrocyclic complexes1. Issue 22 (14th June 2015) - Wang, Hongfeng; Grosjean, Arnaud; Sinito, Chiara; Kaiba, Abdellah; Baldé, Chérif; Desplanches, Cédric; Létard, Jean-François; Guionneau, Philippe
<x xml:space="preserve">Abstract</x> New systems with metal–ligand bond break properties in the initial state are discovered through the investigation of sixteen structures.